2023
DOI: 10.1097/md.0000000000034920
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of acupuncture-related therapy in the treatment of herpes zoster: A network meta-analysis of randomized controlled trials

Jingyu Zhang,
Qiujie Mou,
Zhuxing Wang
et al.

Abstract: Objective: A systematic review and meta-analysis of randomized controlled trials (RCTs) were conducted to evaluate the efficacy and safety of acupuncture-related therapy in the treatment of herpes zoster (HZ) and to provide a reference for the clinical treatment of herpes zoster. Methods: PubMed, Cochrane Library, EMBASE, Web of Science, CNKI, VIP database, Wanfang Database, and SinoMED Chinese and English databases were systematically searched for RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Herpes zoster (HZ) is a common viral infection that arises from the reactivation of the varicella zoster virus ( Kim et al, 2021 ), which is known to remain dormant in the dorsal root ganglion ( De Oliveira Gomes et al, 2023 ). The disease is characterized by the intense inflammation of the affected nerves and skin with a distribution of painful grouped vesicles on an erythematous base ( Zhang J. et al, 2023 ). A population-based study conducted in the United States showed that over 65% of adult patients with HZ were provided with pain medication to alleviate acute herpetic pain ( Lin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herpes zoster (HZ) is a common viral infection that arises from the reactivation of the varicella zoster virus ( Kim et al, 2021 ), which is known to remain dormant in the dorsal root ganglion ( De Oliveira Gomes et al, 2023 ). The disease is characterized by the intense inflammation of the affected nerves and skin with a distribution of painful grouped vesicles on an erythematous base ( Zhang J. et al, 2023 ). A population-based study conducted in the United States showed that over 65% of adult patients with HZ were provided with pain medication to alleviate acute herpetic pain ( Lin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%